PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE DAN STRUKTUR KEPEMILIKAN TERHADAP NILAI PERUSAHAAN: Studi Pada Perusahaan Perbankan yang Terdaftar di BEI Tahun 2018-2021 - Cindy, Atifa; Hidayah, Raudhatul; Syofriyeni, Nini (Unand Press, 2024)
This study aims to examine the influence of good corporate governance proxied by the size of the audit committee, the size of the board of directors, and the size of the board of commissioners, as well as the ownership structure proxied by managerial ownership and institutional ownership on firm value in the banking sector in Indonesia. The research population consists of all banking companies listed on the Indonesia Stock Exchange for the period 2018-2021. The sample was selected using a purposive sampling technique, resulting in 29 companies with a total of 116 observations. This study employs multiple linear regression analysis using SPSS version 23 software. The results indicate that the size of the audit committee, the size of the board of commissioners, managerial ownership, and institutional ownership have a positive and significant effect on firm value. Meanwhile, the size of the board of directors does not affect firm value. Simultaneously, the size of the audit committee, the size of the board of directors, the size of the board of commissioners, managerial ownership, and institutional ownership significantly influence firm value with a coefficient of determination of 16.1%. This study implies that the implementation of good corporate governance and proper ownership structure can enhance the firm value of the banking sector in Indonesia.